Prevalence Of Metabolic Syndrome in Peri and Postmenopausal Women Aged 40- 65 Years in a Tertiary Care Centre (Nepal Medical College Journal, 2024)
Metabolic syndrome (MetS) is a constellation of interrelated risk factors of metabolic origin— metabolic risk factors—that appear to directly promote the development of atherosclerotic cardio-vascular disease (ASCVD). Menopausal transition with its incidental hormonal changes is considered to contribute to the development of MetS. This was a hospital based cross sectional descriptive study conducted in the Obstetrics and Gynaecology department of Nepal Medical College Teaching Hospital, Attarkhel, Gokarneshwor-8, Kathmandu, from the 1st of September 2023 till the 29th of February 2024 after clearance from the IRC (Ref. No: 56-080/081). Convenience sampling was used among women who fulfilled the inclusion criteria. The aim of the study was to determine the prevalence of MetS among the peri and postmenopausal women and to determine which component of the diagnostic criteria of MetS was more strongly associated with MetS in our population. Women were evaluated to have MetS using both the International Diabetes Federation (IDF) and the National Cholesterol Education Program- Adult Treatment Panel III (NCEP-ATPIII criteria). The prevalence of MetS by the IDF criteria was 54% among the perimenopausal women and 61% among the postmenopausal women. Similarly, the prevalence of MetS according to NCEP-ATPIII was 53.5% among the perimenopausal and 65% among the postmenopausal women. All the MetS diagnostic markers showed a strong correlation with MetS (p